2018
DOI: 10.1016/j.prp.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 up-regulation in ampullary adenocarcinoma and its pre-invasive lesions

Abstract: Poor information is available on the molecular landscape characterizing the carcinogenetic process leading to ampullary carcinoma. MiR-21 is one of the most frequently up-regulated miRNAs in pancreatic adenocarcinoma, a tumor sharing similar molecular features with ampullary adenocarcinomas (AVCs), above all with the pancreatic-biliary type. We profiled, by in situ hybridization (ISH), miR-21 expression in a series of 26 AVCs, 50 ampullary dysplastic lesions (35 low-grade [LG-IEN] and 15 high-grade [HG-IEN]) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Locked nucleic acid (LNA) probes with complementarity to miR-122 were labeled with 5′-biotin and synthesized by Exiqon (Vedbaek, Denmark). Tissue microarray (TMA) sections were digested with ISH protease 1 (Ventana Medical Systems, Milan, Italy) and ISH was performed as previously described, with minor modifications [24]. Positive (U6; Exiqon) and negative scrambled LNA probes were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Locked nucleic acid (LNA) probes with complementarity to miR-122 were labeled with 5′-biotin and synthesized by Exiqon (Vedbaek, Denmark). Tissue microarray (TMA) sections were digested with ISH protease 1 (Ventana Medical Systems, Milan, Italy) and ISH was performed as previously described, with minor modifications [24]. Positive (U6; Exiqon) and negative scrambled LNA probes were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Fifty-five primary CRC surgical samples (25 KRAS mutated, 5 BRAF mutated, 10 MMRd) were processed using the Galileo CK3500 Arrayer (www.isenet.it), a semiautomatic and computer-assisted tissue microarray platform, as previously described [30] , [31] . Three tissue cores (1 mm in diameter) were obtained from each considered lesion.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, miR-21 was the most broadly identified miRNA with highest frequency of significances in seven studies and was shown upregulated in ccRCC. It was also found to be upregulated in many other tumors consistently, such as lung cancer (61), B-cell lymphoma (62), gastric cancer (63), prostate cancer (64), colorectal cancer (65), and ampullary adenocarcinoma (66). This implies that miR-21 expression is significantly associated with cancer.…”
Section: Discussionmentioning
confidence: 92%